Moses or Meddler? CMS Missionary J.R. Wolfe in Post-Tianjin Treaty Fujian - Ward, Martin (Mission studies, 2019)
By 1920 Fujian became one of the most missiologically prominent regions in China. This article examines the development of the veteran missionary of the Church Missionary Society, J.R. Wolfe's missiological ideology in relation to the implementation of the Treaty of Tianjin in Fujian from 1862-1878. Amidst considerable frustration at perceived scant manpower and finances commensurate to his evangelistic zeal, he discovered the expedience of consular intervention in cases of persecution and came to seek it as a matter of course. His subsequent experiential epiphany of the British Government's slighting of the articles in the Treaty relating to the safeguarding of the missionary enterprise exacerbated his sense of frustration. This article argues that the disparity between his hagiographical title of "Moses of Fujian" and the controversy surrounding his politicalness is irreconcilable, and that the example of Wolfe demonstrates the complexities of the evolution of missionary ideology and the importance of a thorough archival reappraisal.